Versatile Route for Multifunctional Aerogels Including Flaxseed Mucilage and Nanocrystals. Issue 7 (5th February 2022) - Abdelmonem, Abuelmagd M.; Zámbó, Dániel; Rusch, Pascal; Schlosser, Anja; Klepzig, Lars F.; Bigall, Nadja C.
Abstract: Preparation of low density monolithic and free‐standing organic‐inorganic hybrid aerogels of various properties is demonstrated using green chemistry from a biosafe natural source (flaxseed mucilage) and freeze‐casting and subsequent freeze drying. Bio‐aerogels, luminescent aerogels, and magneto‐responsive aerogels are obtained by combination of the flaxseed mucilage with different types of nanoparticles. Moreover, the aerogels are investigated as possible drug release systems using curcumin as a model. Various characterization techniques like thermogravimetric analysis, nitrogen physisorption, electron microscopy, UV/Vis absorption, and emission spectroscopy, bulk density, and mechanical measurements, as well as in vitro release profile measurements, are employed to investigate the obtained materials. The flaxseed‐inspired organic‐inorganic hybrid aerogels exhibit ultra‐low densities as low as 5.6 mg cm −3 for 0.5% (w/v) the mucilage polymer, a specific surface area of 4 to 20 m 2 g −1, high oil absorption capacity (23 g g −1 ), and prominent compressibility. The natural biopolymer technique leads to low cost and biocompatible functional lightweight materials with tunable properties (physicochemical and mechanical) and significant potential for applications as supporting or stimuli responsive materials, carriers, reactors, microwave‐ and electromagnetic radiation protective (absorbing)‐materials, as well as in drug delivery and oil absorption. Abstract : Bioaerogels, luminescent aerogels, and magneto‐responsive aerogels are obtained by ice‐templating assembly of a bio‐derived biopolymer (flaxseed mucilage) with different types of nanoparticles. Merging the distinct properties of nanoparticles and flaxseed mucilage aerogels, novel low‐cost, biocompatible multifunctional organic‐inorganic hybrid materials with retained physicochemical, enhanced mechanical properties, and reduced health and environment related issues are obtained with significant potential for various applications.